Sistematização da inspeção de código SQL utilizando a técnica stepwise abstraction e a ferramenta CRISTA - Zamboni, Augusto Bindilatti (2015)
Context: Inspections are a software quality assurance activity which can be applied throughout the development process and in different types of artifacts, since it is a statistic activity, based essentially on reading techniques. In the context of source code inspection, a commonly used reading technique is the Stepwise Abstraction (SA). Among the artifacts that comprise a software, the ones related to databases stand out, for instance, SQL source code, of which no reading techniques proposals were identified to support the inspection. Objective: In this setting, this work shows a proposal for systematizing the SQL source code inspection activity using the Stepwise Abstraction technique, with the computational support of the CRISTA tool. Methodology: Due to the shortage of reports and assessment of inspection use in SQL source code in the literature, a survey was developed to identify how the SQL code inspection process is conducted and what the difficulties encountered by IT professionals during its execution are. The survey results provided directives for the development of the systematization proposal for the SQL source code inspection and implementation of new features on the CRISTA tool. An experimental study was conducted to evaluate the feasibility of use for the proposal. Results: The results obtained through the experimental study were satisfactory and show positive indication relating to the feasibility of use for the proposal. When the inspection activity was conducted following the systematizing proposal, 9.3% more defects were found relating to the adhoc approach. Regarding to false positives, the systematization proposal use resulted in zero false positives, while the adhoc approach had two occurrences. Conclusion: Based on these results, the proposal for systematizing the SQL code inspection activity, with the support of the Stepwise Abstraction reading technique and CRISTA tool, showed itself viable for use. In comparison to the adhoc inspection, used in practice, the effectiveness in defects detection increased, while the number of false positives decreased. Additionally, it should be noted the research relevance for the software engineering area, taking into account the shortage of studies related to the SQL code inspection in the literature.